The effects of genome expansion on transposable element diversity in salamanders - Haley, Ava, author; Mueller, Rachel, advisor; Sloan, Daniel, committee member; Stenglein, Mark, committee member (Colorado State University. Libraries, 2021)
Transposable elements (TEs) are repetitive sequences of DNA that replicate and proliferate throughout genomes. Taken together, all the TEs in a genome form a diverse community of sequences, which can be studied to draw conclusions about genome evolution. TE diversity can be measured using ecological models for species distribution that consider richness and evenness of communities. It is currently not well studied how genome expansion impacts the diversity of transposable elements. However, there are a few models that predict TE diversity decreasing as genomes expand due to varying mechanisms such as selection against ectopic recombination and competition between TEs and silencing machinery. Salamanders are known to have some of the largest vertebrate genomes. Salamanders of the genus Plethodon in particular have very large genomes consisting of high levels of TEs, with sizes ranging from 30 to 70 Gigabases (Gb). Here, I use Oxford Nanopore sequencing to generate low-coverage genomic sequences for four species of Plethodon that encompass two independent genome expansion events, one in the eastern clade and one in the western clade: Plethodon glutinosus (41.4 Gb), P. cinereus (30.5 Gb), P. idahoensis (71.7 Gb), and P. vehiculum (50.5 Gb). I classified the TEs in these datasets using RepeatMasker and DnaPipeTE and found ~51 superfamilies which accounted for 27-32% of the genomes. For each genome I calculated the Simpson's and Shannon's diversity indices to quantify diversity, taking into account both TE richness and evenness. In all cases, the values for Simpson's index were within 0.75 and 0.79, and for Shannon's index all species were within 1.88 and 1.99. We conclude that once genomes reach large sizes, they maintain high levels of TE diversity at the superfamily level, in contrast to observations made by previous studies done on smaller genomes.